Úloha a význam FANCD2 proteinu - Altmannová, Veronika, 1983- (2007)
Fanconi anemia belongs to a group of rare human genetic diseases and is frequently associated with bone marrow failure, high predisposition to cancer and birth defects. The cells from Fanconi anemia’s patients are hypersensitive to crosslinking agents (e.g. diepoxybutane or mitomycin C), and show an increased frequency of chromosome breakage. To date, thirteen complementations groups (FANCA, -B, -C, -D1, -D2, -E, -F, -G, -I, -J, -L, -M, and -N) have been associated with Fanconi anemia. It has been also demonstrated that all proteins encoded by FA genes cooperate in common pathway, called as FA or FA/BRCA pathway. After DNA damage or during S-phase, eight FA proteins (A, B, C, E, F, G, L, and M) asssemble in a multisubunit nuclear complex (FA core complex), which is required for monoubiquitination of FANCD2 at lysine 561. The monoubiquitinated isoform of FANCD2 is targeted to DNA damage-induced nuclear foci where it colocalizes and interacts with other proteins participating in DNA re.